NIKAH MUT{âAH SEBAGAI ALTERNATIF HUKUM PERKAWINAN ISLAM: Telaah terhadap Pemikiran Sudirman Tebba (Justicia Islamica, 2012)
NIKAH MUT{âAH SEBAGAI ALTERNATIF HUKUM PERKAWINAN ISLAM: Telaah terhadap Pemikiran Sudirman TebbaÂ Khusniati RofiâahÂ Abstract: Islamic law as a social âinstitutionâ (pranata sosial) is substantively to control society and to response amount of problems which human does. Mujtahids as Islamic creative thinkers should have standard competence to reformulate and to anticipate problems appear at their community. Sudirman Tebba, who often studies many problems such as zina (âillegal sexual relations), is one of Islamic law creative tinkers in Indonesia. According to him, illegal sexual relations do not impact of liberal culture merely. It can be effect of both bureaucracy system and legal law officers. Tebba recommends nikah mutâah as a solution to this problem. Nikah mutâah, which muslim community does at early Islam, is a procedur to legalize nikah. Theoretically, nikah mutâah is contrary to functional structural as Talcot Person theorizes. Person states that family structure, individually, has a function and position.There is a limitation of time for Nikah mutâah. So a husband will not be at his functional position. Tebba statement, will probably ease people to legalize their marriage, but it at the other hand will affect bigger negative problems. It is a contra productive to Islamic law, which takes care of and protects humanities. This short article is to show how functional structural theory sees nikah mutâah as Islamic law works, and what does it implication to society in Indonesia.Â Â Â  Â Â Keywords: Islamic law, Nikah mutâah, functional structural